A Leading Routing Mechanism for Neighbor Content Store - Chuanzhen Du; Julong Lan; Ming Tian (Dianxin kexue)
It is very easy for the nodes in named data networking to ignore the neighbor nodes. To solve this issue, a leading routing mechanism for neighbor content store was proposed. Firstly, through building the interest clusters, the nodes were partitioned to different reigns to announce the information of content store. Secondly, the packets and the fast routing tables were designed. Finally, the best path was chosen to send the interest packets. The theoretical analysis and simulation results show that, this mechanism adequately uses the neighbor content and effectively decreases the average network delay. The server load is reduced by 30%.